Indicadores da qualidade do solo em função do uso da terra - Luz, Felipe Bonini (2017)
Land-use change (LUC) or land use has been largely responsible for a large part of carbon dioxide emissions and soil degradation. The increased demand for bioenergy has led to the expansion of sugarcane areas in the south-central region, especially in areas previously used as pasture, and increased demand for food has expanded the use of marginal soils (i.e, sandy). In this way, the native vegetation gave place to the areas with pastures and, later, the transformed pastures in fields for the production of grains or bioenergy. However, despite the high positive economic impact for the country through the production of soybeans and sugarcane, it is not known how this LUC is affecting the resources and the quality of the soil. For this, in this work the indicators to evaluate soil quality under different land uses in the tropical transition region of southern Brazil were measured. Four land uses (native vegetation, pasture, sugarcane, and soybean) were evaluated in three sites with different soil conditions. The hypothesis tested in this study was that intensification of agriculture through pasture management, soybean cultivation under no-tillage system (NT), integrated crop-livestock system (ICLS) and sugarcane improved soil quality. Soil samples were collected in three layers (0.0 - 0.10, 0.10 - 0.20, 0.20 -0.30 m) in Londrina, Santo Inácio and São Jorge do Ivaí, northern- PR- Brazil. Physical, chemical, biological attributes, stocks of carbon and nitrogen were analyzed in the laboratory. A Soil Quality Index (SQI) was also calculated using the Soil Management Assessment Framework (SMAF). The results point to the enormous potential of soil carbon sequestration through NT, ICLS and pasture management, especially in the marginal areas in the process of agricultural expansion in Brazil. In addition, it was concluded that land use with soybean and sugarcane does not induce physical and chemical degradation of the soil in relation to pasture, but the low carbon and nitrogen inventory in the soil, and the lower SQI, the expansion of sugarcane should be avoided in sandy soils.